Comparison of multilocus variable-number tandem-repeat analysis and whole-genome sequencing for investigation of Clostridium difficile transmission. - Eyre, D; Fawley, W; Best, E; Griffiths, D; Stoesser, N; Crook, D; Peto, T; Walker, A; Wilcox, M (2013)
No study to date has compared multilocus variable-number tandem-repeat analysis (MLVA) and whole-genome sequencing (WGS) in an investigation of the transmission of Clostridium difficile infection. Isolates from 61 adults with ongoing and/or recurrent C. difficile infections and 17 asymptomatic carriage episodes in children (201 samples), as well as from 61 suspected outbreaks affecting 2 to 41 patients in 31 hospitals in the United Kingdom (300 samples), underwent 7-locus MLVA and WGS in parallel. When the first and last samples from the same individual taken for a median (interquartile range [IQR]) of 63 days (43 to 105 days) apart were compared, the estimated rates of the evolution of single nucleotide variants (SNVs), summed tandem-repeat differences (STRDs), and locus variants (LVs) were 0.79 (95% confidence interval [CI], 0.00 to 1.75), 1.63 (95% CI, 0.00 to 3.59), and 1.21 (95% CI, 0.00 to 2.67)/called genome/year, respectively. Differences of >2 SNVs and >10 STRDs have been used to exclude direct case-to-case transmission. With the first serial sample per individual being used to assess discriminatory power, across all pairs of samples sharing a PCR ribotype, 192/283 (68%) differed by >10 STRDs and 217/283 (77%) by >2 SNVs. Among all pairs of cases from the same suspected outbreak, 1,190/1,488 (80%) pairs had concordant results using >2 SNVs and >10 STRDs to exclude transmission. For the discordant pairs, 229 (15%) had ≥2 SNVs but ≤10 STRDs, and 69 (5%) had ≤2 SNVs but ≥10 STRDs. Discordant pairs had higher numbers of LVs than concordant pairs, supporting the more diverse measure in each type of discordant pair. Conclusions on whether the potential outbreaks were confirmed were concordant in 58/61 (95%) investigations. Overall findings using MLVA and WGS were very similar despite the fact that they analyzed different parts of the bacterial genome. With improvements in WGS technology, it is likely that MLVA locus data will be available from WGS in the near future.